LIVESTOCK IN NUTRITION AND FOOD SECURITY IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
In theory, animals that reproduce together transform undesirable, low-value substances into milk, meat, and eggs to increase their food supply. The people consume 13% of the world's energy on a regular basis, which basically increases food security. Despite the fact that they are pricey sources of energy, "creature source food blends" are one of the most amazing sources of protein and micronutrients, which are essential for daily life and good health. The test is a way to look at difficult tradeoffs so that good results from controlled animals should be clear while bad ones, like risks to people's health and the environment, are limited.